2018
DOI: 10.1038/s41556-018-0174-4
|View full text |Cite
|
Sign up to set email alerts
|

m6A mRNA methylation regulates AKT activity to promote the proliferation and tumorigenicity of endometrial cancer

Abstract: N-methyladenosine (mA) messenger RNA methylation is a gene regulatory mechanism affecting cell differentiation and proliferation in development and cancer. To study the roles of mA mRNA methylation in cell proliferation and tumorigenicity, we investigated human endometrial cancer in which a hotspot R298P mutation is present in a key component of the methyltransferase complex (METTL14). We found that about 70% of endometrial tumours exhibit reductions in mA methylation that are probably due to either this METTL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
564
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 645 publications
(581 citation statements)
references
References 62 publications
(81 reference statements)
16
564
0
1
Order By: Relevance
“…Nevertheless, expression of METTL3 is reduced in endometrial carcinoma, which stimulates AKT signaling and promotes tumor growth and invasiveness both in vitro and in vivo (53). Mechanistically, lower expression of METTL3 reduces m 6 A methylation, restrains YTHDF1-promoted translation of PHLPP2, a negative AKT regulator, while dampens YTHDF2promoted decay of transcripts encoding mTORC2, which is a positive AKT regulator.…”
Section: Mettl3mentioning
confidence: 99%
“…Nevertheless, expression of METTL3 is reduced in endometrial carcinoma, which stimulates AKT signaling and promotes tumor growth and invasiveness both in vitro and in vivo (53). Mechanistically, lower expression of METTL3 reduces m 6 A methylation, restrains YTHDF1-promoted translation of PHLPP2, a negative AKT regulator, while dampens YTHDF2promoted decay of transcripts encoding mTORC2, which is a positive AKT regulator.…”
Section: Mettl3mentioning
confidence: 99%
“…This SNP is an eQTL located within intron 2 of SYNPO2, and is reported to loop to the promoter of SYNPO2 80 and METTL14 81 , a component of N6-methyladenosine (m6A) methyltransferase complex. This complex controls post translational modification of m6A RNA and has been implicated in cancer, cell differentiation and proliferation in development pathways 82 . Interestingly, m6A is reported to be enriched in the 3'UTR 83 , which was the most significantly enriched biofeature in our partitioning of heritability analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant activation of AKT signaling has been widely implicated in many cancers . Although it is well known that AKT activity is regulated through phosphorylation, some other types of post‐translational modifications, such as ubiquitination, SUMOylation, acetylation, and m6A mRNA methylation, have also been reported to promote AKT activity and function . Recently, it was reported that AKT ubiquitination is correlated with its phosphorylation level, suggesting that ubiquitination represents a novel post‐translational modification that plays a key role in AKT activation .…”
Section: Discussionmentioning
confidence: 99%
“…27,28,30 Although it is well known that AKT activity is regulated through phosphorylation, some other types of post-translational modifications, such as ubiquitination, SUMOylation, acetylation, and m6A mRNA methylation, have also been reported to promote AKT activity and function. 31,32 Recently, it was reported that AKT ubiquitination is correlated with its phosphorylation level, suggesting that ubiquitination represents a novel post-translational modification that plays a key role in AKT activation. 33 Consistent with these reports, our data indicated that, in addition to ubiquitination, the ectopic expression of TRAF6 wt but not TRAF6 E3-ligase-deficient mut could also significantly facilitate AKT phosphorylation.…”
Section: Discussionmentioning
confidence: 99%